Building a Vehicle To Control Specialty Pharmacy Costs - HAVENS, JANE (BioCommunications LLC, 2004)
The trend lines skewing those reports on your desk indicate an ominous upward arc in specialty drug expenditures. Top management at the health insurer you work for tells you, ‘Do something about it.’ The author and her team responded with an innovative approach that effectively addresses coding issues, internal buy-in, and keeping members happy.